Regulación de la esporulación y la biosíntesis de cefalosporina C por la subunidad GaI de una Proteína G heterotrimérica de Acremonium chrysogenum - Cruz Ramón, Jessica Yazmín (Universidad Autónoma Metropolitana, 2018)
The filamentous fungus Acremonium chrysogenum is the natural producer of the β-lactam antibiotic cephalosporin C (CPC) and is as such used worldwide in the industrial production of this antibiotic. Albeit its profound industrial importance, there is still a limited understanding about the molecular mechanisms regulating CPC biosynthesis in this fungus. Fungal heterotrimeric G proteins regulate different processes related to development, such as colony growth and asexual sporulation, the main mechanism of propagation in filamentous fungi. In addition, it has been reported that heterotrimeric G proteins, and specifically the group I G subunit (GI) control secondary metabolite biosynthesis. In order to study the function of the GαI subunit of A. chrysogenum (Aga1) in morphogenesis and CPC biosynthesis, we obtained transformants with plasmid pC43aga1G42R, which contains an aga1 mutant allele: aga1G42R. For comparison purposes the pG42Rb plasmid (García-Rico et al., 2007) was included in this work. The plasmid pG42Rb, just as pC43aga1G42R plasmid, contains a mutated allele of the GαI subunit gene of Penicillium chrysogenum (pga1G42R). In both cases, the mutation results in a constitutively activated GαI subunit. The phenotype of transformants Aga1G42R and Pga1G42R clearly showed that the GαI subunit plays an important role in the vegetative development of the fungus, and is essential for the formation of arthrospores, a morphological type associated with the production of CPC. Constitutive activation of Aga1 (aga1G42R) caused a reduction in conidia production with respect to the wild type strain (ATCC 11550). Moreover, all aga1G42R transformant strains showed an early biosynthesis of pigments. The aga1G42R allele caused also a reduction in CPC biosynthesis, indicating that high levels of Gα-GTP negatively regulate both conidiation and CPC biosynthesis in A. chrysogenum.